Os Principais bancos brasileiros poderiam ter quebrado após o resultado eleitoral de 2014 ? - Figueiredo Neto, Cândido Bezerra de (2015)
The scenario of uncertainty in Brazilian capital market, during the election period, contributed to the formation of volatility clusters, that made it difficult to pricing of the securities traded on the Brazilian stock exchange. In this context, this research aims to investigate if this scenario of uncertainty could have led to the breakdown of some of the largest Brazilian banks with open market. The actions of the banks analyzed were: Bank of Brazil ON,Bradesco PN and ItaúUnibanco PN. The metric for this research was to Value-at-Risk (VaR).Two models that are said unconditional as regards the variance: unconditional Gaussian VaR and VaR Best Fitting unconditionally. The other two are called conditional models, assuming that the volatility varies over time. The best metric that represented the time series by Backtesting was conditional Logistic VaR. From the estimation of the best model, it was identified that the banks would not break, but could have accumulated significant devaluation.